Cloning and evaluation of different constitutive promoters in the oleaginous yeast Rhodosporidium toruloides. Issue 3 (14th January 2016) - Wang, Yanan; Lin, Xinping; Zhang, Sufang; Sun, Wenyi; Ma, Sijia; Zhao, Zongbao Kent
Abstract: The oleaginous yeast Rhodosporidium toruloides is an unconventional yeast species that can accumulate a high content of lipids. Because it belongs to the basidiomycetous group of fungus, limited tools and functional elements are available for genetic engineering of R. toruloides and related red yeasts. Here we report the functional evaluation of five constitutive promoters from this yeast. We assembled a reporter gene expression cassette, consisting of a promoter, the hygromycin gene (HYG) and the nos terminator, and inserted it into the binary vector pZPK. Hygromycin‐resistant transformants were obtained when R. toruloides cells were co‐cultured with Agrobacterium tumefaciens AGL1 cells harbouring the engineered vector. Genomic integration of the reporter cassette was verified by successful amplification of target DNA fragments. Quantitative PCR analysis suggested that the transformant had only one copy of the reporter cassette. The strength of these promoters was demonstrated at the phenotypic level on the hygromycin‐gradient plate and at the transcriptional level by real‐time quantitative PCR. It was found that the strengths of these promoters varied no more than five‐fold and followed a decreasing sequence of PPGI, PPGK, PFBA, PTPI, and PGPD . This study established new genetic elements for the construction of superior R. toruloides strains to produce advanced biofuels and related chemicals. Copyright © 2015 John Wiley & Sons, Ltd.